MATLAB Simulation of Solar PV & Concentrating Solar Power Plant (CSP) as a Renewable Energy Sources: Comparative Analysis of Solar PV and Concentrating Solar Power Plants (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper presents the importance of concentrating solar power plant compare to other renewable energy sources like solar PV cells, wind power generation, ocean thermal energy etc. we discuss the basic concept an introduction of concentrating solar power plant their working and types of components used for concentrating the solar energy. Day by day the use of solar energy is increased all over world, so it is necessary to study about solar energy. Still to date solar PV cells type solar power plant used in solar energy but due to their lower efficiency (near about 14-18) use of concentrating solar plant is come into picture. In our paper we will discuss about its demand and advantages compared to other solar PV cells. In this paper we will design the solar thermal power plant into the matlab-simulink and SAM (System Advisor Model) software. We are comparing the PV cell type solar power plant to CSP plant using the results of matlab-simuink design.